Phase Segregation during Processing of Semi-Solid Slurry by Rheocasting Method SEED - Stunová, Barbora Bryksí; Bryksí, Vlastimil (Manufacturing Technology Journal, 2015)
The paper describes specific phenomena of semi-solid casting process, especially rheo-casting method SEED, which uses mechanical swirling for reaching proper structure in semi-solid state. The eutectic segregation during processing of semi-solid slurry can cause specific casting defects. Heat treated alloy AlSi7Mg0.3 was applied for producing castings. For observing structure, metallographic observation by light and SEM microscopy was used as well as spectral analysis.
Keywords: Semi-Solid; Rheo-Casting; Phase Segregation; Aluminium Alloys; Casting Defects